Agent-based fault tolerant distributed event system - Sahingoz, Ozgur Koray; Sonmez, A. Coskun (SLOVAK ACAD SCIENCES INST INFORMATICS, 2007)
In the last years, event-based communication style has been extensively studied and is considered a promising approach to develop large scale distributed systems. The historical development of event based systems has followed a line which has evolved from channel-based systems, to subject-based systems, next content-based systems and finally type-based systems which use objects as event messages. According to this historical development the next step should be usage of agents in event systems. In this paper, we propose a new model for Agent Based Distributed Event Systems, called ABDES, which combines the advantages of event-based communication and intelligent mobile agents into a flexible, extensible and fault tolerant distributed execution environment.
Keywords: distributed event system; fault tolerance; agvent; agent event; advertisement; based routing; publish/subscribe systems; Computer Science